Chemical mechanical polishing exploiting metal electrochemical corrosion of single-crystal SiC. (December 2022) - Luo, Yingrong; Xiong, Qiang; Lu, Jiabin; Yan, Qiusheng; Hu, Da
Abstract: A chemical mechanical polishing (CMP) method of single-crystal SiC is proposed based on metal electrochemical corrosion. The oxidation mechanism of SiC by electrochemical corrosion of metals and the mechanism of surface material removal are revealed by corrosion and polishing experiments. The metallic aluminum sheet that is in contact with single-crystal SiC was immersed in sodium sulfate (Na2 SO4 ) electrolyte solution, and the morphological and elemental changes of single-crystal SiC surface were examined by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS). Then, polishing experiments were conducted on single-crystal SiC using different metal polishing discs and different polishing solutions. The XPS and EDS results show that single-crystal SiC can electrochemically corrode to generate a silica reaction layer. The use of metal polishing discs in CMP significantly improved the material removal rate (MRR) of SiC, with the highest MRR of 1011.43 nm/h for aluminum polishing discs, followed by that for iron polishing discs, and the lowest MRR for copper and alumina ceramic polishing discs. When metal polishing discs were used, the addition of electrolyte solution significantly improved the MRR and reduced the surface roughness of the SiC surface. Polishing with Na2 SO4 solution when the polishing disc was aluminum disc, the MRR was higher than that for using deionized water by 105%, and the surface roughness Ra decreased by 37.8% to 2.8 nm. The metal electrochemical corrosion reaction can promote the oxidation of single-crystal SiC and generate a soft SiO2 reaction layer on the SiC surface, thereby improving the polishing efficiency of single-crystal SiC. Highlights: A CMP method of single-crystal SiC is proposed based on metal electrochemical corrosion. The oxidation mechanism of single-crystal SiC based on metal electrochemical corrosion. was investigated. The material removal mechanism of CMP exploiting metal electrochemical corrosion of single-crystal SiC was studied.